Analisis Bentuk Lagu Nyanyian Penanian Dolo Berjudul “Allo Lendu’ Bulan Lendu’” - Rinda Lorensa Kombong; Slamet Haryono; Malarsih Malarsih (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This research was conducted to analyze the structure of the song entitled "Allo Lendu' Bulan Lendu'" which is part of the Penanian dolo song in Gandangbatu Sillanan Toraja at death ceremonies which is starting to fade because of the new songs in Church services. Researchers used a qualitative research method with an ethnomusicological approach. Based on the results of data analysis, it was found that the song "Allo Lendu' Bulan Lendu'" has a similar melody to the Song of the Congregation No. 331 entitled “Day, Night, Season, Year”. The form is in the form of two parts of sentences A and B, so that the pattern is AB=A(a, ​​a') B(b,a'). The motif is relatively simple and full of repetition, as can be seen from each melody form which literally repeats the motif from the melody theme.